Optimizing topical drop efficacy with proper eyelid positioning - Yu Xia; Nathaniel A. Blecher; Philip L. Custer; Erin G. Sieck (American Journal of Ophthalmology Case Reports)
Purpose: To report the observation that the efficacy of topical glaucoma treatment improved after surgical correction of ectropion in a 71-year-old male with a known history of glaucoma. Observations: The patient initially presented for tearing and lid malposition and was found to have bilateral elevated intraocular pressures (IOP) in addition to bilateral lower eyelid ectropion. IOP control was initially prioritized over ectropion repair, with IOP remaining elevated despite topical glaucoma treatment and selective laser trabeculoplasty. Sequential unilateral ectropion repair was then carried out, with topical glaucoma treatment resumed after the first repair. It was observed that the IOP improved with topical glaucoma treatment on each side after ectropion repair, despite no changes to medications nor dosing. Conclusions and importance: The efficacy of topical glaucoma treatment is dependent on drop availability and absorption. While recent efforts to increase drop efficacy have been focused on engineering formulations that increase retention or corneal penetration, our case highlights that in selected glaucoma patients, correction of lid malposition may serve as an effective way to improve drop efficacy.